Towards engineering application: Integrating current strategies of promoting direct interspecies electron transfer to enhance anaerobic digestion - Xinyue Jiang; Zhiqiang Zhao; Yaobin Zhang (Chemical Engineering Journal Advances, 2022)
The study present here was to integrate the current engineering strategies of promoting direct interspecies electron transfer (DIET), ethanol-type fermentation pretreatment, and conductive materials (zero-valent iron [ZVI] and graphite) supplemented, to strengthen the anaerobic digestion of kitchen wastes. Experimental results imply that after ethanol-type fermentation pretreatment, ZVI and graphite supplemented could significantly improve the methane production, transformation efficiency of organic matter, as well as impact resistance ability of systems during anaerobic digestion of kitchen wastes with a gradual increase of organic loading rate. The sludge with ZVI and graphite addition had a relatively higher capacitance and lower resistance than that without ZVI and graphite. With the concentration ratio of ZVI and graphite increasing, the evidently increased abundance of electrotrophic methanogens, Methanosarcina acetivorans, and Methanospirillum hungatei suggested that ZVI stimulated the growth of electrotrophic methanogens. Together with the enrichment of exoelectrogens capable of extracellular electron transfer (e.g., Streptococcus, Petrimonas, and Syntrophomonas species) in the presence of ZVI and graphite, the DIET between these exoelectrogens and electrotrophic methanogens might be responsible for the improved performances and stability.